(3cdGe Gddg GdeYLR (B:s (3aUhd aj OQGSI GdEYLGR GdbQBfj (B/s - (3aQMGJ, CMeO Rcjs ((3GdbGgQI (B- (3LeghQjI eUQ GdYQHjI (B:s (3eQcR JHUjQ dJbQjH GdJQGK hGdQO Ydi GdTHgGJ (B:s (3OGQ GdEeGe GdHQHgGQj ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3cdGe Gddg GdeYLR (B: (3aUhd aj OQGSI GdEYLGR GdbQBfj(B) (3hGdPj bGe HJCdjag (B((3CMeO Rcj aQMGJ(B) (3aj MhGdj (B(188) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3EYLGR GdbQBf(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdaUd GdChd (B: (3GdbQBf gh GdeYLRI GdNGdOI, GdaUd GdKGfj (B: (3GdEYLGR GdUhJj GdbQBfj, GdaUd GdKGdK (B: (3GdEYLGR GdUQaj GdbQBfj, GdaUd GdQGHY (B: (3GdEYLGR aj GdfXe GdbQBfj, GdaUd GdNGeS (B: (3GdEYLGR GdOdGdj GdbQBfj(B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B175-182.s
Keywords: (3bQBfs -- (3eHGMK bQBfjI YGeIs -- (3EYLGR dZhjs -- (3EYLGR bQBfjs